(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Global population is increasing at a rapid rate in past some decades. Rapid increase in population creates pressure on resources. Land is one of resources which is also showing impact. Land is important resource only 29 % of the earth surface is covered with land among this 29% some of the land is covered with snow, desert, forest, mountains which is not useful for human activities or for human residence. Land is used for various purposes population increase can affect the land use land cover of an area. This global population increase also has major impact such as urbanization. Urbanization is a global phenomenon which affect land use land cover of an area. Urbanization is population shift from rural to urban residence. Due to the development of I’T parks and automobile industry people are migrating towards Pune city which leads to haphazard & unplanned development of Pune city to its outskirts areas. However, this leads to change in the land use land cover of Pune city. It will have impact on the natural vegetation cover as well as on the agricultural area. The present study is mainly focuses on the changing land use land cover pattern of Pune city. The main objective of this study is to assess land use land cover change of Pune city over three decades (2001-2021) and its impact on vegetation cover. The spatiotemporal study of land use land cover (LULC) is carried out for three decades 2001 to 2021 using remotely sensed multi temporal LANDSAT and LISS III Resourcesat-1 satellite data and analyzes this data by using modern technology like Remote Sensing (RS) and Geographical Information System (GIS). By analyzing this data, it has been found that amount of built-up area has increased dramatically whereas the area under agricultural as well as natural vegetation cover has been decreased. Uncontrolled urbanization and land use land cover change raises many environmental issues like loss of agricultural land, loss of animal habitat, loss of natural vegetation cover. So that monitoring of urbanization is play very important role for planned development of cities which will help to protect environment.